2012
DOI: 10.1088/0004-637x/762/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Global Dynamics of Subsurface Solar Active Regions

Abstract: We present three-dimensional numerical simulations of a magnetic loop evolving in either a convectively stable or unstable rotating shell. The magnetic loop is introduced in the shell in such a way that it is buoyant only in a certain portion in longitude, thus creating an Ω-loop. Due to the action of magnetic buoyancy, the loop rises and develops asymmetries between its leading and following legs, creating emerging bipolar regions whose characteristics are similar to the ones of observed spots at the solar su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 73 publications
(106 reference statements)
8
42
0
Order By: Relevance
“…This means that a given sunspot group is never energized as a whole. These three observational properties are actually consistent with the solar convection-driven breaking of large sub-photospheric flux tubes into a series of smaller deformed structures, as found in numerical simulations (Fan et al 2003;Jouve et al 2013). They show that these deformed structures should eventually emerge through the photosphere as grouped but distinct magnetic bipoles.…”
Section: Taking Into Account the Fragmentation Of Fluxsupporting
confidence: 83%
“…This means that a given sunspot group is never energized as a whole. These three observational properties are actually consistent with the solar convection-driven breaking of large sub-photospheric flux tubes into a series of smaller deformed structures, as found in numerical simulations (Fan et al 2003;Jouve et al 2013). They show that these deformed structures should eventually emerge through the photosphere as grouped but distinct magnetic bipoles.…”
Section: Taking Into Account the Fragmentation Of Fluxsupporting
confidence: 83%
“…They were originally reported by López Fuentes et al (2000) and observed later in other works (see, e.g., Li et al, 2007;Chandra et al, 2009;Luoni et al, 2011). Their presence in emerging flux-ropes has been found by numerical simulations (Archontis and Hood, 2010;MacTaggart, 2011;Jouve, Brun, and Aulanier, 2013). Luoni et al (2011) compared the helicity-sign inferred from the orientation of magnetic tongues, observed in line-of-sight magnetograms, with other known helicity sign proxies for a sample of 40 ARs.…”
Section: Introductionmentioning
confidence: 65%
“…The origin of the twisted magnetic flux-ropes in the corona is most probably related to a combination of flux-emergence, magnetic shearing by surface motions, and magnetic reconnection in the corona, but the exact details are unknown at present (Jouve & Brun 2009;Fan et al 2009;Jouve et al 2013;Pinto & Brun 2013). We only considered here the dynamics of already existing coronal flux-ropes that have reached typical coronal background temperatures.…”
Section: Scope and Caveats Of The Modelmentioning
confidence: 99%